Intensive labour supply: A menu choice revealed preference approach for German females and males - Klaus Beckmann; Nele E. Franz; Andrea Schneider (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
This paper deals with discrete labour supply decisions of different groups of persons in response to a change in net wage rates. The centrepiece of this approach is individuals' switching between working time categories, while facing switching costs that arise when people expand or reduce working hours. We define a degree of persistence of individual behaviour as well as its complement, labour supply mobility. Using the German Socio-Economic Panel (SOEP), we estimate persistence and mobility by gender and type of household.
Keywords: H31; J22; C25; 330; labour mobility; discrete choice approach; labour supply elasticities